Effect of silane treatment on the mechanical properties of polyurethane/water glass grouting materials. (30th July 2016) - He, Zhenglong; Li, Qifeng; Wang, Junwei; Yin, Ning; Jiang, Shuai; Kang, Maoqing
Graphical abstract: Highlights: The PU/WG grouting materials modified with CTS were synthesized. The incorporation of 2.5 wt% CTS in WG dramatically improved the mechanical properties of PU/WG hybrid materials. A probable mechanism of the functions of CTS in the PU/WG grouting material was proposed. Abstract: In this study, silane coupling agent 3-chloropropyltrimethoxysilane (CTS) was used for improving the distribution of water glass (WG) in the polyurethane (PU) matrix and increasing the crosslinking density of PU/WG grouting materials. The optimum dosage of CTS and the pretreatment time of WG were investigated. The effect of CTS on the surface property of WG and the fracture morphology of the PU/WG composites was studied by contact angle measurement and scanning electron microscopy, respectively. The effect of CTS on the mechanical properties of PU/WG grouting materials was systematically studied by compression test, fracture mechanical test, flexural test and dynamic mechanical analysis. The introduction of CTS in the PU/WG grouting materials improved the surface property of WG, the homogeneous distribution of polysilicate particles in PU matrix, the compressive property of PU/WG composites by 11.65–40.65%, the fracture toughness by 9.68%, the fracture energy by 21.33%, the flexural strength by 6.60%, the flexural modulus by 15.85%, and the dynamic mechanical properties of the composites. A possible mechanism of the functions of CTS in the PU/WG grouting materials was proposed.